Non-occupational exposure to asbestos is the main cause of malignant mesothelioma in women in North Jutland, Denmark - Vasiliki Panou; Mogens Vyberg; Christos Meristoudis; Johnni Hansen; Martin Bøgsted; Øyvind Omland; Ulla Møller Weinreich; Oluf Dimitri Røe (Nordic Association of Occupational Safety and Health (NOROSH), 2019)
OBJECTIVES: Diffuse malignant mesothelioma (MM) is mainly caused by asbestos inhalation. The malignancy is rare among women and studies of the prevalence and causative role of non-occupational asbestos exposure among women with MM are scarce. This observational study aimed to elucidate the asbestos exposure patterns among women with MM. METHODS: All histological and cytological specimens from women diagnosed with MM between 1974-2015 at the Institute of Pathology, Aalborg University Hospital in Denmark, were re-evaluated. Occupational and habitation information were obtained from Danish registries and medical journals based on record linkage via the unique person ID. The number of MM cases in each parish in the region of North Jutland was determined and the incidence density in parishes was used to calculate the spatial relative risk (RR) of MM among women. RESULTS: Diagnosis of MM was confirmed in 91 women. Exposure types were classified as occupational (9%), domestic (10%), environmental (22%), combination of domestic and environmental (34%) and unknown (25%). Twenty continuous parishes formed a MM "hotspot" around the asbestos-consuming industries in the city of Aalborg. Of these, the maximum RR was found in a parish housing an asbestos factory [RR 10.5, 95% confidence interval (CI) 5.5-19.4, environmental exposure in particular RR 2.9, 95% CI 0.7-6.1]. CONCLUSION: Non-occupational asbestos exposure is the main cause of MM and may account for up to 66% of MM cases among women in North Jutland, Denmark.